Changes in norepinephrine transporter expression in models of Alzheimer´s disease - Parviainen, Petra (My University, 2020)
Alzheimer´s disease (AD) is the most common form of dementia. AD can be associated with malfunction of the brain norepinephrine transporter (NET) and degeneration in the locus coeruleus (LC) which will reduce norepinephrine (NE) secretion. We aimed to study the changes in NET expression in aging animal models of AD. Transgenic APP/PS1-21 mice and TgF344-AD rats were used as animal models of AD. Their healthy age matched litter mates were used as wild type (WT) controls. The NET binding radiotracer [18F]NS12137 was used for in vivo dynamic positron emission tomography (PET) scans and autoradiographic (ARG) studies. Immunohistochemistry (IHC) was used to quantify NET expression in mice brain. [18F]NS12137 derived 18F-radioactivity was also measured from the major peripheral organs. In vivo PET showed slower [18F]NS12137 brain uptake in mice than in rats. Brain region-to-cerebellum ratios showed higher uptake in the older TgF344-AD rats compared to the young. ARG studies revealed lower LC-to-cerebellum ratios in old TgF344-AD and WT rats when compared to young rats. No significant differences in [18F]NS12137 uptake were observed in hippocampus-, neocortex- and thalamus-to-cerebellum ratios between old and young or age matched TgF344-AD and WT rats. IHC showed increased NET expression associated to the amyloid plaques. Peripheral uptake of 18F-radioactivity was highest in excretory organs and bone in both rats and mice. [18F]NS12137 is able to detect a decrease in NET expression in LC in aging TgF344-AD rats. More studies are needed to demonstrate significant differences in aging AD animals in other areas of the brain.